Prescription for social dilemmas : psychology for urban, transportation, and environmental problems - Fujii, Satoshi, 1968- (Springer, 2017)
This book provides a theoretical, empirical, and pragmatic understanding of social dilemmas (SDs). A SD is a social situation where cooperation maximizing collective or social profit is different from defection maximizing individual profit. Problems arise when too many group members choose to pursue individual profit and immediate satisfaction rather than behave in the group's best long-term interests. The problems include an environmental problem and various types of urban, economic, and political problems. Most books treating SDs are not monographs but are proceedings or omnibus volumes written by different researchers. Few monographs have been published for SDs, but those few deal only with basic theories and empirical findings. This book, by contrast, is a monograph by a single author and provides complete coverage from basic theories in Part I to applied theories and pragmatic solutions for urban, transportation, and environmental problems in Parts II and III. Various types of strategies are proposed in this book to overcome the problems caused by SDs in various situations based on the basic theories of those dilemmas. The strategies are psychological and structural ones. The book includes theories, empirical evidence in experiments, and practical policies in the real world for these strategies. Thus, the work effectively provides a bridge between basic behavioral scientists, applied behavioral scientists, and practitioners. With this useful source, basic scientists will understand how to apply their scientific knowledge to the real world and also will encounter new scientific problems that should be solved scientifically. Applied researchers and specialists will become familiar with new solutions through basic research on SDs and will be made aware of new pragmatic problems that should be solved with a practical approach.